Hypoalbuminemia, influenza vaccination and other factors related to the development of pneumonia acquired outside hospitals in southern Japan: A case–control study. Issue 2 (5th February 2015) - Washio, Masakazu; Kondo, Kyoko; Fujisawa, Nobumitsu; Harada, Eiji; Tashiro, Hideki; Mizokami, Tetsuya; Nogami, Hiroko; Iwanaga, Tomoaki; Nakanishi, Yoichi; Suzuki, Kanzo; Ohfuji, Satoko; Fukushima, Wakaba; et al.
Abstract : Aim: Pneumonia is the third largest cause of death in Japan. Pneumonia continues to be one of the most common causes of morbidity, hospitalization and mortality, especially in the elderly. The aim of the present study was to evaluate the factors related to the development of pneumonia acquired outside hospitals among the Japanese elderly. Methods: We carried out a hospital‐based, case–control study. Cases were patients who had been newly diagnosed with pneumonia acquired outside hospitals. For each case, one to three controls were defined as outpatients with other diseases (not pneumonia) at the same hospitals. All participants (i.e. 50 cases and 110 controls) were aged 65 years and older. Results: Compared with control participants, hypoalbuminemia (<3.5 g/dL) and low body mass index (<18.0) were more common in pneumonia patients, whereas the proportion of those who could go out by themselves (i.e. self‐support in activities of daily living) and the vaccination rate of seasonal influenza were lower in patients with pneumonia than control participants. Even after controlling for age, sex, hospital and aforementioned four factors, hypoalbuminemia (OR 9.19, 95% CI 3.70–22.81) increased the risk of pneumonia, whereas seasonal influenza vaccination (OR 0.37, 95% CI 0.16–0.85) reduced the risk. Even after excluding those who lived in a nursing home, hypoalbuminemina (OR 12.19, 95% CI 4.29–34.63) increased the risk of pneumonia. Conclusions: Hypoalbuminemia might be a risk factor for pneumonia among the elderly living in the community.Geriatr Gerontol Int 2016; 16: 223–229.